2014
DOI: 10.1017/s1047951113002151
|View full text |Cite
|
Sign up to set email alerts
|

Airway compression management in late-presenting absent pulmonary valve syndrome

Abstract: Most late-presenting patients with absent pulmonary valve syndrome do not have airway compression. Either pulmonary artery reduction plasty or the Lecompte manoeuvre can relieve proximal airway compression, without a significantly different risk of pulmonary artery reintervention between techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This is probably because the decision to provide mechanical relief in these patients was related to their PA size, which is also a marker of the severity of intrinsic airway disease. We believe that PA plasty or the LeCompte manoeuvre is essential to treat proximal airway compression as described in the literature [12,27] but may not effectively relieve distal bronchi compression.…”
Section: Discussionmentioning
confidence: 93%
“…This is probably because the decision to provide mechanical relief in these patients was related to their PA size, which is also a marker of the severity of intrinsic airway disease. We believe that PA plasty or the LeCompte manoeuvre is essential to treat proximal airway compression as described in the literature [12,27] but may not effectively relieve distal bronchi compression.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, bronchoscopy may be important for treatment decisions in children with absent pulmonary valve syndrome. 34 Both papers underscore the importance of early cooperation of the pediatric bronchoscopist with other subspecialties in the treatment of complex disease.…”
Section: Flexible Bronchoscopy: Therapeutic Applicationsmentioning
confidence: 99%
“…This paper reported that in one of seven cases the observed bronchial compression during test angioplasty was so severe that it was decided not to place a pulmonary artery stent. Similarly, bronchoscopy may be important for treatment decisions in children with absent pulmonary valve syndrome . Both papers underscore the importance of early cooperation of the pediatric bronchoscopist with other subspecialties in the treatment of complex disease.…”
Section: Diagnostic Testing/endoscopymentioning
confidence: 99%